2013
DOI: 10.1248/bpb.b13-00079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Aquaglycero-Aquaporins: Its Potential for Cancer Characterization

Abstract: Aquaglycero-aquaporins (agAQPs) are one of the water channel proteins located in the cell membrane that transport not only water but also some small solutes such as glycerol. Since agAQPs are involved in cancer proliferation and malignancy, it might be possible to utilize them as new targets for cancer molecular imaging. In this study, we investigated whether agAQPs can be specifically targeted by using [14 C]-labeled glycerol ([ 14 C]glycerol), which passes through agAQPs. In the in vitro experiments, compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For example, the chronic myeloid leukemia cell line (K562) is recognized less sensitive towards iAs III treatment because of lacking adequate expression of AQP9 [69]. Moreover, when AQP3 gene was knocked down in human lung adenocarcinoma cell line (CL3), it was found that the CL3 cells became more resistant to iAs III [70], indicating the AQPs are at least involved in cellular susceptibility towards iAs III .…”
Section: Influences Of Arsenic Potential For Toxicity and As Anticancmentioning
confidence: 99%
“…For example, the chronic myeloid leukemia cell line (K562) is recognized less sensitive towards iAs III treatment because of lacking adequate expression of AQP9 [69]. Moreover, when AQP3 gene was knocked down in human lung adenocarcinoma cell line (CL3), it was found that the CL3 cells became more resistant to iAs III [70], indicating the AQPs are at least involved in cellular susceptibility towards iAs III .…”
Section: Influences Of Arsenic Potential For Toxicity and As Anticancmentioning
confidence: 99%
“…The involvement of AQP9 in glycerol transportation continues to draw attention from researchers, and now it has been extended to cancer research. In several cancer cell lines, the expression of AQP9 was related to the uptake of [14C]-labeled glycerol [ 138 ]. Another experiment in a rat hepatocellular carcinoma model found that the expression of AQP9 was present at a low level before tumorigenesis, while it was significantly increased in the early stage of hepatocellular carcinoma.…”
Section: Functions In Cancermentioning
confidence: 99%
“…The potential beneficial use of AQP3 inhibitors or modulators (decreasing AQP3 expression) remains to be evaluated for cancer treatment. In addition, radiolabeled glycerol could be used as a molecular probe targeting aquaglyceroporins to estimate their expression in different tissues in vivo , including tumors ( Saito et al, 2013 ).…”
Section: Aquaglyceroporins As Drug Targets For Metabolic Diseasesmentioning
confidence: 99%